Stacked‐Layer Heterostructure Films of 2D Thiophene Nanosheets and Graphene for High‐Rate All‐Solid‐State Pseudocapacitors with Enhanced Volumetric Capacitance. Issue 3 (15th November 2016) - Wu, Zhong‐Shuai; Zheng, Yijun; Zheng, Shuanghao; Wang, Sen; Sun, Chenglin; Parvez, Khaled; Ikeda, Taichi; Bao, Xinhe; Müllen, Klaus; Feng, Xinliang
Abstract : Stacked‐layer heterostructure films of 2D thiophene nanosheets and electrochemically exfoliated graphene are constructed for ultrahigh‐rate all‐solid‐state flexible pseudocapacitors and micro‐supercapacitors with superior volumetric capacitance due to the synergetic effect of the ultrathin pseudocapacitive thiophene nanosheets and the capacitive electrochemically exfoliated graphene.